Implementasi Kebijakan Restrukturisasi Kredit Perbankan kepada Usaha Mikro, Kecil Dan Menengah di Era Pandemi Covid-19 pada PT. Bank Rakyat Indonesia (Persero) - Derriansya Putra Jaya; Kgs. M. Sobri; Raniasa Putra; Abdul Najib (Universitas Medan Area, 2023)
This article aims to analyze the implementation of banking credit restructuring policy for Micro, Small, and Medium Enterprises (MSMEs) during the COVID-19 pandemic at PT. Bank Rakyat Indonesia (Persero). The focus of the research is on the aspect of implementing banking credit restructuring policy. To comprehend this issue, the theoretical framework proposed by Ripley and Franklin is employed, which emphasizes three key aspects: (1) the level of bureaucracy's compliance with higher-level regulations, (2) the smooth execution of routines without hindrances, and (3) the achievement of goals and intended impacts of all existing programs. A qualitative approach is utilized to explore and understand the perspectives of individuals and groups involved in this social issue. Data collection is conducted in two phases, with the first involving direct observation, documentation, and in-depth interviews to achieve the research objectives. Data analysis adopts a descriptive approach with qualitative methods, including data condensation, data display, and verification. The study concludes that the implementation of banking credit restructuring policy for MSMEs during the COVID-19 pandemic, as examined in the case study at BRI KCU Palembang A Rivai in Palembang City, aligns with the framework proposed by Ripley and Franklin. This research provides valuable insights into how the policy is executed and its impact on the MSME sector. Therefore, this article has the potential to contribute significantly to the understanding and improvement of banking credit restructuring policy implementation in the future.